2006
DOI: 10.1038/sj.bjc.6602956
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human Kallikrein 14 (KLK14) in breast cancer is associated with higher tumour grades and positive nodal status

Abstract: Human kallikrein 14 (KLK14) is a steroid hormone-regulated member of the tissue kallikrein family of serine proteases, for which a prognostic and diagnostic value in breast cancer has been suggested. To further characterise the value of KLK14 as a breast tumour marker, we have carefully analysed KLK14 expression in normal breast tissue and breast cancer both on the RNA level by real-time RT-PCR (n ¼ 39), and on the protein level (n ¼ 127) using a KLK14-specific antibody for immunohistochemistry. We correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 28 publications
1
26
0
4
Order By: Relevance
“…KLK14 and KLK4 mRNA positivity is associated with high tumor grade and size (122,123) . In accordance with the mRNA data, strong immunohistochemical KLK14 staining of the malignant breast tumors is linked to aggressive phenotypes of the disease (124) .…”
Section: Other Malignancies Breast Cancermentioning
confidence: 48%
“…KLK14 and KLK4 mRNA positivity is associated with high tumor grade and size (122,123) . In accordance with the mRNA data, strong immunohistochemical KLK14 staining of the malignant breast tumors is linked to aggressive phenotypes of the disease (124) .…”
Section: Other Malignancies Breast Cancermentioning
confidence: 48%
“…Recently, numerous studies demonstrated the elevated expression of AGR2 in various human preneoplasic states (30) and cancers including those of the esophagus (37), prostate (38 -41), pancreas (42), lung (43), breast (25,27,44), and biliary system (26), thus showing that it is a widely overexpressed protein in human carcinomas. This might indicate that several experimental and pathophysiological systems could be necessary to tackle the precise molecular and cellular functions of AGR2.…”
Section: Discussionmentioning
confidence: 99%
“…This protein, which contains a pseudo thioredoxin domain, is encoded by an estrogen receptor-responsive gene. AGR2 is found in various cancers to be overexpressed in precancerous states and is indicative of a bad prognosis (25)(26)(27)(28)(29)(30). However the molecular roles played by AGR2 remain unclear.…”
Section: Proteomics Analysis Of Ribosome-associated Proteins In the Er-mentioning
confidence: 99%
“…Consequent to its secretion, KLK14 forms a constituent of seminal plasma (10) and sweat (14) and is present in its catalytically active form in the stratum corneum of the skin (13)(14)(15). Furthermore, aberrant KLK14 expression has been detected in patients with breast (7,10,11,16), ovarian (7,9,10), prostate (7,17), and testicular (7) cancers and peeling skin syndrome (18), at the tissue and/or serum level. Correlative clinical data have also linked elevated KLK14 mRNA expression with aggressive forms of breast (11,16) and prostate cancer (17) and with the prognosis of breast (16) and ovarian (9) cancer patients.…”
mentioning
confidence: 99%
“…Subsequent studies demonstrated that the KLK14 gene is under steroid-hormone regulation (9,10) and is most highly expressed in the glandular epithelia of the breast (10,11) and prostate (8,10) and in the epidermis (i.e. stratum granulosum) and appendages (i.e.…”
mentioning
confidence: 99%